Indigenous Bacillus spp. ability to growth promoting activities and control bacterial wilt disease (Ralstonia solanacearum) - YULMIRA YANTI; TRIMURTI HABAZAR; REFLINALDON REFLINALDON; CHAINUR RAHMAN NASUTION; SRIMANO FELIA (Society for Indonesian Biodiversity, 2017)
Yanti Y, Habazar T, Reflinaldon, Nasution CR, Felia S. 2017. Indigenous Bacillus spp. ability to growth promoting activities and control bacterial wilt disease (Ralstonia solanacearum). Biodiversitas 18: 1562-1567. Among the species of Plant Growth Promoting Rhizobacteria, Bacillus spp. has been found to provide beneficial effects to different plant species. Based on our previous research from in planta screening’s method, we found six indigenous strains of Bacillus spp., which had the ability to control bacterial wilt and increased growth and yields of chili. Those were Bacillus subtilis BSn5,q Bacillus sp. RD-AZPVI-03, Bacillus sp. Y81-1, B.cereus strain C38/15, B.cereus strain APSB-03, and B. subtilis strain CIFT-MFB-4158A. This research aimed to characterize the mechanism of selected Bacillus spp. as biocontrol agents of R. solanacearum and as biofertilizer of chili in vitro. We have observed the biocontrol characters (production of HCN, siderophore, biosurfactant, protease, root colonization, and antibiotic), and biofertilizer’s characters (production of Indole Acetic Acid (IAA), ammonia and phosphate solubilization) of Bacillus spp. All strains had ability to produce variable concentrations of IAA, B.subtilis strain CIFT-MFB-4158A can produce siderophore, all isolates cannot produce HCN and biosurfactant, 4 isolates can produce protease. Based on the ability to colonize roots, B.subtilis strain CIFT-MFB-4158A had the best ability to colonize root surface (4.17 x 105 CFU/g root), while B. subtilis BSn5 had the best ability to colonize internal roots (2.08 x 105 CFU/g), and 2 Bacillus strains can suppress R. solanacearum in vitro.